Ecosystem duties, green infrastructure, and environmental injustice in Los Angeles. Issue 1 (18th October 2021) - Randle, Sayd
Abstract: In Los Angeles, water managers and environmentalist NGOs champion green infrastructure retrofits, installations intended to maximize the water‐absorbing capacity of the urban landscape. In such arrangements, the work of water management is necessarily spread among a more‐than‐human community, including (but certainly not limited to) humans, plants, soils, and gravels. This article analyzes the human labor within these collaborations, tracking when and how this work gets enrolled in networks of water management and circuits of value. I develop the term ecosystem duties to characterize these exertions and as a useful analytic for assessing emergent dynamics of environmental justice. Resumen: En Los Ángeles, los administradores de agua y las ONGs ambientalistas, abogan por la actualización del diseño de la infraestructura verde, instalaciones destinadas a maximizar la capacidad de absorber agua del paisaje urbano. En tales arreglos, el trabajo del manejo del agua está necesariamente distribuido entre una comunidad más que humana, incluyendo (pero ciertamente no limitada a) humanos, plantas, suelos y gravillas. Este artículo analiza el trabajo humano dentro de estas colaboraciones, siguiendo cuándo y cómo este trabajo se inscribe en las redes de manejo y circuitos de valor. Desarrollo el término deberes ecosistémicos para caracterizar estos esfuerzos y como información útil para evaluar la dinámica emergente de justicia ambiental. [ trabajo ecológico, servicios ecosistémicos, infraestructura, manejo de aguas, justicia ambiental ]